The teaching of nature sciences during the pandemic of Covid-19: challenges and possibilities in public and private schools (Research, Society and Development, 2022)
Introduction: The Covid-19 pandemic directly interfered in school education, where educators and students had to reinvent themselves from the moment schools closed their doors to face-to-face teaching. In this sense, technology plays an important role in minimizing the impacts experienced during the pandemic. Objective: analyze the teachers’ conceptions about the teaching of Natural Sciences and their difficulties for the classroom teaching process, and the analysis of practical classes in remote times as tools for assimilating content and whether they contributed in a relevant way in the teaching-learning process of students in the pandemic. Methodology: this work was carried out with teachers in the area of natural sciences working in basic education at two schools, being a public school in the state of Pernambuco and a private school in the state of Minas Gerais. Considerations: It is necessary to invest in initial and continuing training of basic education teachers, in favor of better preparation for teaching work today. It is extremely important to invest in public policies aimed at this type of training, as well as in the best technological support for that class, and for the students, who also need to be in-depth and prepared for a possible event that allows for social distancing.